SMART VILLAGE READINESS USING DECISION TREE ANALYSIS THE CASE OF BANYUMAS REGENCY INDONESIA - Ali Rokhman; Tobirin Tobirin; Muslih Faozanudin (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Digital transformation is now inevitable for anyone, individually and organizationally, including village government organizations. Therefore, the village government must be ready to transform into a smart village. The smart village component consists of smart government, smart environment, smart economy, smart mobility, smart people, and smart living. This study aims to analyze the readiness of local communities for smart villages. This research uses quantitative methods, where the population is local people. Kalikidang Village, located in Sokaraja, Banyumas regency, was used as a case study. The number of respondents was 20, taken through proportional random sampling techniques. Data analysis techniques use decision trees that are processed through Rapidminer software. The results showed that individual characteristics significantly influence the readiness of smart villages where the domicile attribute is the most influential